2007
DOI: 10.1097/01.ta.0000198214.24056.40
|View full text |Cite
|
Sign up to set email alerts
|

Household Firearm Ownership and Rates of Suicide Across the 50 United States

Abstract: Household firearm ownership levels are strongly associated with higher rates of suicide, consistent with the hypothesis that the availability of lethal means increases the rate of completed suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
125
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 229 publications
(140 citation statements)
references
References 39 publications
14
125
0
1
Order By: Relevance
“…A positive and significant association exists between levels of household firearm ownership and rates of firearm and overall suicide; rates of non-firearm suicide were not associated with levels of household firearm ownership." (Miller et al, 2007). The findings are "consistent with the hypothesis that the availability of lethal means increases the rate of completed suicide."…”
Section: Environmental Risk Factor Managementsupporting
confidence: 80%
See 1 more Smart Citation
“…A positive and significant association exists between levels of household firearm ownership and rates of firearm and overall suicide; rates of non-firearm suicide were not associated with levels of household firearm ownership." (Miller et al, 2007). The findings are "consistent with the hypothesis that the availability of lethal means increases the rate of completed suicide."…”
Section: Environmental Risk Factor Managementsupporting
confidence: 80%
“…The findings are "consistent with the hypothesis that the availability of lethal means increases the rate of completed suicide." (Miller et al, 2007). This study controlled for the presence of serious mental illness and substance abuse and dependence (among other factors), to avoid any error that could be induced if individuals with these illnesses are more likely to own guns which could be used to end their lives.…”
Section: Environmental Risk Factor Managementmentioning
confidence: 99%
“…As in a smaller study of northeast states for which deliberate self-harm data were available (91), this study found in both crude and multivariate analyses, among men and women and in every age group, that states with higher rates of household gun ownership had higher rates of firearm suicide and overall suicide. The study showed no association between firearm ownership rates and nonfirearm suicide (92).…”
Section: Cross-sectional Studiesmentioning
confidence: 86%
“…Just as the distribution of mortality rates for lung cancer accounts for a significant proportion of the variation in mortality from cancer overall, suicide mortality rates in the United States appear to be driven largely by rates of firearm suicide (86,88,91,92). For example, Figure 2 shows that suicide rates in rural areas of the United States are considerably higher than in urban areas: The most urban areas have mortality rates of less than 10 per 100,000 residents, compared with rates of more than 14 per 100,000 residents in the most rural areas.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
See 1 more Smart Citation